Erratum: Zalameda, J. et al. Detection and Characterization of Damage in Quasi-Static Loaded Composite Structures using Passive Thermography. Sensors 2018, 18, 3562 - Joseph Zalameda; William Winfree (Sensors, 2018)
The authors wish to correct Table 3 in their paper published in Sensors [...]